Caveolin-1 regulates chemokine receptor 5-mediated contribution of bone marrow-derived cells to dermal fibrosis - Lee, Rebecca; Perry, Beth; Heywood, Jonathan; Reese, Charles; Bonner, Michael; Hatfield, Corey M.; Silver, Richard M.; Visconti, Richard P.; Hoffman, Stanley; Tourkina, Elena (Frontiers in Pharmacology, 2014)
In fibrotic diseases caveolin-1 underexpression in fibroblasts results in collagen overexpression and in monocytes leads to hypermigration. These profibrotic behaviors are blocked by the caveolin-1 scaffolding domain peptide (CSD) which compensates for caveolin-1 deficiency. Monocytes and fibroblasts are related in that monocytes are the progenitors of fibrocytes (CD45+/Collagen I+ cells) that, in turn, are the progenitors of many fibroblasts in fibrotic tissues. In an additional anti-fibrotic activity, CSD blocks monocyte differentiation into fibrocytes. We studied a mouse fibrosis model (Pump Model) involving systemic bleomycin delivery that closely models scleroderma (SSc) in several ways, the most important of which for this study is that fibrosis is observed in the lungs, skin, and internal organs. We show here that dermal thickness is increased 2-fold in the Pump Model and that this effect is almost completely blocked by CSD (p < 0.001). Concomitantly, the subcutaneous fat layer becomes >80% thinner. This effect is also blocked by CSD (p < 0.001). Even in mice receiving vehicle instead of bleomycin, CSD increases the thickness of the fat layer. To study the mechanisms of action of bleomycin and CSD, we examined the accumulation of the chemokine receptor CCR5 and its ligands MIP1α and MIP1β in fibrotic tissue and their roles in monocyte migration. Fibrocytes and other leukocytes expressing CCR5 and its ligands were present at high levels in the fibrotic dermis of SSc patients and Pump Model mice while CSD blocked their accumulation in mouse dermis. Migration toward CCR5 ligands of SSc monocytes and Pump Model bone marrow cells was 3-fold greater than cells from control subjects. This enhanced migration was almost completely blocked by CSD. These results suggest that low monocyte caveolin-1 promotes fibrosis by enhancing the recruitment of fibrocytes and their progenitors into affected tissue.